PENDIDIKAN KARAKTER DISIPLIN PADA SANTRI PONDOK PESANTREN SLAF TERPADU BAHJATUR ROGHIBIIN KUDUS - Istyi Nihayati; Erik Aditia Ismaya; Ika Oktavianti (Sekolah Tinggi Pariwisata Mataram, 2021)
Discipline character is the awareness that arises from the innermost inner self of humans to follow and obey the rulesnd also legal vakues that apply in the unit of the environment they occupy. The Bahjatur Roghibiin integrated Salaf Islamic Boarding Scool is a place to educate good discipline character see from the attitudes and abilities of the students. In this study to implementation of disciplinary character of the students in integrated salaf Islamic boarding school Bahjatur Roghibiin Kudus. This study uses a qualitative research approach with case study rsearch type. The results of study stated that salaf education found by the researchers in the recitation activities is an activity that refers to the “ kitab kuning” and uses several methods such as “bendongan or wetonan” memorization,” sorogan” and “batsul al-masail” which are used in each activity.